2014
DOI: 10.1002/jwmg.670
|View full text |Cite
|
Sign up to set email alerts
|

Post‐fledging survival in passerine birds and the value of post‐fledging studies to conservation

Abstract: Conservation efforts are most effective when we have complete demographic information for a species of concern. Nevertheless, fundamental gaps in our knowledge of demography still exist for many taxa. For passerine birds, the period of time directly after young birds leave the nest and before they disperse and/or migrate (i.e., the post‐fledging period) remains an understudied life stage. We reviewed the literature on survival of passerine birds during the post‐fledging period to synthesize current knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
235
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(257 citation statements)
references
References 108 publications
9
235
4
Order By: Relevance
“…The postfledging mortality we observed is consistent with other studies that have demonstrated that mortality rates are highest in the first day after fledging (e.g., Tome and Denac 2012) and then steadily decrease (Naef-Danzer and Grüebler 2016), with most mortality occurring in the first week (Lloyd and Martin 2016). The estimated postfledging survival to 21 days of Yellow Warblers is also similar to those estimated for the closely related Hooded Warbler, Setophaga citrina, (0.23, Rush and Stutchbury 2008;0.57 Eng et al 2011) and within the range of estimates obtained from 31 studies on songbirds in North and South America (range = 0.23 -0.87; Cox et al 2014). …”
Section: Discussionsupporting
confidence: 68%
“…The postfledging mortality we observed is consistent with other studies that have demonstrated that mortality rates are highest in the first day after fledging (e.g., Tome and Denac 2012) and then steadily decrease (Naef-Danzer and Grüebler 2016), with most mortality occurring in the first week (Lloyd and Martin 2016). The estimated postfledging survival to 21 days of Yellow Warblers is also similar to those estimated for the closely related Hooded Warbler, Setophaga citrina, (0.23, Rush and Stutchbury 2008;0.57 Eng et al 2011) and within the range of estimates obtained from 31 studies on songbirds in North and South America (range = 0.23 -0.87; Cox et al 2014). …”
Section: Discussionsupporting
confidence: 68%
“…Below, we discuss the biological implications and methodological underpinnings behind the observed age and latitude effects on survival. It is well known that survival of juveniles varies throughout the first weeks of life, being lowest during the first 3 wk after fledging and subsequently increasing (Anders et al 1997, Tarwater et al 2011, Cox et al 2014, Naef-Daenzer and Grüebler 2016; however, after that initial, risky phase, it was not sufficiently clear whether survival of postfledging first-year birds was indeed lower than that of adults. Furthermore, if such a difference exists, it is important to know its magnitude, because it will help us understand whether a possible latitudinal variation in juvenile survival may explain the persistence of a latitudinal gradient in clutch size.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the change in estimated population growth when we incorporated postfledging survival rates into juvenile survival was much more pronounced for Acadian Flycatchers than for Ovenbirds, suggesting that the importance of postfledging mortality to population models of forest breeding migratory songbirds varies among species. The addition of a postfledging component to nesting studies, even for just 2 weeks postfledging, would greatly improve our understanding of potential tradeoffs between the nesting and postfledging period associated with habitat or landscape (Cox et al 2014; however, see Dybala et al 2013). Tysdal.…”
Section: Discussionmentioning
confidence: 99%
“…This is further complicated because the majority of Neotropical migrant songbirds do not return to their natal area, making annual juvenile survival, an important vital rate affecting populations, difficult to measure (Anders and Marshall 2005). Nesting and postfledging are the 2 distinct juvenile life stages that occur on the breeding grounds, but we have a much better understanding of factors affecting survival during nesting than during postfledging (Cox et al 2014). We can improve our ability to assess population viability and forecast population growth under different scenarios with a better understanding of the factors that limit population parameters in each stage of the annual cycle.…”
Section: Introductionmentioning
confidence: 99%